2018
DOI: 10.1177/0040517518801154
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of high-performance microfiber synthetic leather base using thermoplastic polyurethane/sulfonated polysulfone electrospun nanofibers

Abstract: Compared to natural leather, microfiber synthetic leather has many excellent qualities, such as chemical resistance and physical and mechanical properties. However, preparation of microfiber synthetic leather with a high water vapor transmission rate (WVT), moisture absorption and wearing comfort property is still a challenge. In this study, we prepared thermoplastic polyurethane (TPU)/sulfonated polysulfone (SPSf) electrospun nanofibers and applied them to a microfiber synthetic leather base (MSLB). The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The wet toilet wipe on the market (non-woven) was made of non-degradable chemical synthetic fibers, which showed the smooth cylindrical surface ( Fig. 5 d) and excellent mechanical properties due to the inherent excellent mechanical properties of chemically synthesized fibers [ 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The wet toilet wipe on the market (non-woven) was made of non-degradable chemical synthetic fibers, which showed the smooth cylindrical surface ( Fig. 5 d) and excellent mechanical properties due to the inherent excellent mechanical properties of chemically synthesized fibers [ 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that the fineness of the fiber has an important influence on the softness of MSLB. The addition of nanofibers reduced the bending rigidity of the fiber [22]. Therefore, the softness of MSLB was improved.…”
Section: Resultsmentioning
confidence: 99%
“…prepared thermoplastic polyurethane (TPU)/sulfonated polysulfone (SPSf) electrospun nanofibers and applied them to a MSLB. The results showed that with the increase of nanofiber content from 0 to 30%, WVT was increased by 55.9%, moisture absorption was increased by 26.25% and softness was increased by 88.55% [22]. However, the effect of fiber fineness on the performance of MSLB was not discussed in the previous study of simulating natural leather.…”
Section: Introductionmentioning
confidence: 99%
“…Since the structure of nonwoven fabric used in ultra-fine fiber is similar to that of bundled collagen fibers in natural leather, the solidified and reduced PU coating has an open microporous structure, which produces microfiber leather similar to natural leather in terms of microstructure and appearance. With better physical and mechanical performance and better air and moisture permeability, as well as better chemical resistance, hydrophobicity, and mildew resistance, it is one of the best alternatives to natural leather [ 133 , 134 , 135 ].…”
Section: Applications Of Pu In Leather/synthetic Leathermentioning
confidence: 99%
“…With improved standards of living, the demand for high-performance, high-quality, and eco-synthetic leather continues to rise. Hence, synthetic leather will develop in the direction of ecological and functional synthetic leather that combines the advantages of good physical properties, multifunctionality, and eco-friendliness [ 133 , 136 , 137 ].…”
Section: Applications Of Pu In Leather/synthetic Leathermentioning
confidence: 99%